PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 036 SINTONG KECAMATAN TANAH PUTIH - Lilik Pindiyanti; Eddy Noviana; Zetra Hainul Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the low of IPA’s learning results of students, with an average grade of 64.5, while the value of minimum completeness criteria (KKM) Subject IPA SDN 036 Sintong Tanah Putih is 70. Of the 18 class IV SDN 036 Sintong Tanah Putih, students who completed as many as 8 peoples, while not complete as many as 10 peoples. This research is a classroom action research (PTK) is done to improve IPA’s learning outcomes Class IV SDN 036 Sintong Kecamatan Tanah Putih by applying inquiry learning method. Data collection instruments in this study is the teacher’s activities sheet, student’s activities sheets and achievement test. This study presents the results obtained from the value of learning semester prior to action by an average of 64.5 and an increase in UH I in Cycle I to 69.17. In the UH II Cycle II was increased again to 80.83. The activities of teachers in the learning process at the first cycle the first meeting is 50% and at the second meeting increase to 62.5%. At the first meeting of the second cycle of teacher’s activitie increased to 70.83% and in the second meeting of the second cycle increased to 83.33%. Similarly, analysis of student’s activities at the first meeting of the first cycle was 41.66% and increased in the second meeting of the cycle I to 58.33%. At the first meeting of the second cycle of student’s activities is 66.66% and at the second meeting of the second cycle increased to 79.16%. Results of the study in class IV SDN 036 Sintong Tanah Putih prove that the application of inquiry learning methods to improve IPA learning outcomes Class IV SDN 036 Sintong Tanah Putih.Keywords: inquiry learning model, IPA learning outcomes2